Pelatihan Praktikum Biokimia Konsep Uji Kandungan Urine pada Mahasiswa Program Studi Kebidanan Stikes Tanawali Persada Kabupaten Takalar - Taiyeb, Mushawwir; Hartono, Hartono; Ismail, Ismail; Junda, Muhammad; Suryani, A. Irma (Universitas Negeri Makassar, 2022)
Education curriculum D3 Midwifery Stikes Tanawali Persada Kab. Takalar has basic courses such as biochemistry courses which provide knowledge about the ability to perform screening and analysis, however, it is not accompanied by giving practicums to equip students with basic skills. Therefore, basic training related to screening and diagnosis skills, such as urine biochemical examination, was carried out. The community groups that were used as partners in this training were students majoring in midwifery, Stikes Tanawali Persada, Takalar Regency. The training method planned in this training activity consists of three stages. The first stage is in the form of providing material and information regarding the technique of analyzing the content of chemical compounds in urine samples. The second stage is the implementation of the practical analysis of the content of chemical compounds in urine samples. The third stage is discussion and evaluation. The result of this training activity was successful and smooth. Participants' understanding also increased based on the results of the evaluation given at the end of the training. This success was achieved due to careful preparation and support from various parties, especially the manager and teaching staff of Stikes Tanawali Persada Takalar Regency who have provided adequate training facilities and infrastructure and support from experienced presenters and practicum assistants.